Effects of low-level laser therapy on orthodontic tooth movement: a randomised clinical trial - Shahid, Fazal (2020)
The purpose of this study was to evaluate the effects of low-level laser therapy (LLLT) on Little Irregularities Index, acceleration of tooth movement, dental arch dimensional changes, pain perception, inter radicular and buccolingual bony changes, root resorption, bone densities and chairside time in orthodontic extraction cases using self-ligating and conventional bracket systems with three-dimensional (3D) evaluation via cone beam computed tomography (CBCT) and digital dental models (DDM). A randomised clinical trial was performed with a total of thirty-two patients (eight patients in each group) with the mean age of 22.41 (4.18) years. The patients were further divided in four groups randomly [A= self-ligating laser (SLL), B = conventional bracket laser (CBL), C = self-ligating non laser group (SLNL), D = conventional non laser bracket (CBNL)]. A 940 nm wavelength laser device (iLase; Biolase, Irvine, Calif) was used. Laser irradiation applied for both upper and lower incisors and canine tooth for 6 seconds at mesial and distal side of apical, middle, mesial and distal side of cervical area with 100mW laser output and energy density was 75J/cm2 per tooth. Patient’s pre-treatment and at the end of levelling and alignment stage, the CBCT and DDM acquisition were taken and measured via Planmeca RomexisTM Software 2.3.1.R (Helsinki, Finland). DDM assessed the acceleration of tooth movement and dental arch dimensional changes. The root resorption, inter radicular, buccolingual bony changes and bone densities measured via CBCT acquisitions of patients. Visual analogue scale (VAS) was given to the patients to record their pain intensity for seven days. The normality of the data was evaluated with the Shapiro–Wilk test. Intra-class correlation (ICC) coefficient test was applied to check the reliability for all the variables. For the intragroup comparison, the paired sample t-test and Wilcoxon signed-rank test were performed. Descriptive statistic was applied for assessment of pain perception based on the different wire placement up to seven consecutive days. For the intergroup comparison, regardless of a bracket system and LLLT application, an independent t-test and Mann Whitney test were performed. One-way ANOVA with Post Hoc Bonferroni correction and Kruskal Wallis with pair wise comparison were performed to assess the comparison of four groups. The intraclass correlation (ICC) values for intra and inter-examiner reliability were in the range of excellent correlation of all variables. Most of the variables showed significant differences in intra group comparison. However, few variables exhibited significant differences during intergroup comparison regardless of the bracket system (acceleration of tooth movement, root resorption on 22, bone density on CM11, AD11) and LLLT application (mandibular IMW, pain on 0.017×0.025 NiTi wire and bone density on MM33, CD31, CD 41, MP33). Moreover, when comparing all four groups, significant difference (P<0.05) observed in accelerating tooth movement, inter radicular bony changes (42 to 41 for CBNL vs CBL), pain (0.014 NiTi archwire), bone density (AM22, AD12, CP21, AM42, MM33) and chairside time. Other variables showed no significant differences. In conclusion, LLLT group needed less mean time to complete levelling and alignment than the non LLLT group. LLLT does not affect dental arch dimensional changes, inter radicular and buccolingual bony changes, root resorption and bone density. Bracket system has no effects on the acceleration of the tooth movement, dental arch dimensional changes, orthodontic pain, inter radicular, buccolingual bony changes, root resorption and bone density. Self-ligating bracket takes less chair side time compared to the conventional bracket.